Revisiting Polygamy in the Qur'an: A Futuristic Interpretation in Dialogue with Ancient Middle Eastern Culture - Latifah, Ainiyatul; Vikriadi, Khalid; Doloh, Aubaidillah (Universitas Muhammadiyah Surakarta, 2025)
This study re-examines the Qur'anic discourse on polygamy in the context of the patriarchal social structures of ancient Middle Eastern societies, where women were often regarded as property and denied bodily autonomy. Within this historical setting, the Qur'an introduced a significant ethical intervention by limiting the practice of polygamy and imposing a strict condition of justice. This restriction was not a validation of male privilege, but a moral correction aimed at gradually reforming an unequal social order. The result of this research has been collected through a qualitative method by using the scriptures as main sources. A transdisciplinary and futuristic hermeneutical approach has helped the authors in analyzing how the Qur'an allows polygamy with certain conditions for the sake of gender equality. The researchers emphasize a contextual and progressive moral framework responding social change which has not been discussed by previous research. It also recognizes the possibility of future shifts in human and ecological conditions that may influence the ethical balance of gender relations.